KESADARAN HUKUM MASYARAKAT TENTANG PENGELOLAAN SAMPAH DI DESA PATAMPANUA, KECAMATAN MATAKALI, KABUPATEN POLEWALI MANDAR - Rifdan, Rifdan; Suyitno, Imam; Rahman, Hasan Sas (Jurnal Tomalebbi, 2024)
This research aims to determine (1) Community legal awareness regarding waste management in Patampanua Village, with indicators (a) knowledge of the law, (b) understanding of the law, (c) views on the law and (d) actions towards the law. (2) the role of the village head in forming community legal awareness of waste management in Patampanua Village. This research is a qualitative survey research, the types of data used in this research are primary data and secondary data. Data collection techniques were obtained by observation, interviews and documentation. The focus of this research is community legal awareness and the role of the village head regarding waste management in Patampanua Village. The research results show (1) Community legal awareness in Patampanua village regarding waste management is still low. In the first indicator, people show a desire for the rule of law, but in the second indicator, their knowledge of these rules is very minimal. The third indicator highlights that the public's view of laws related to waste management is also limited. Furthermore, in the fourth indicator, community action against the law shows a tendency to dispose of waste not in accordance with applicable regulations. (2) Patampanua Village faces challenges in waste management. Even though the village head has carried out outreach, there is an assessment that these efforts are not yet fully relevant. Legal regulations regarding waste management are still lacking, and although there have been positive steps such as providing rubbish bins and the presence of daily officers, information regarding waste management is not yet provided to the public.